Diet in Medieval Gaelic Ireland: A multiproxy study of the human remains from Ballyhanna, Co. Donegal. (September 2020) - McKenzie, Catriona J.; Murphy, Eileen M.; Guiry, Eric; Donnelly, Colm J.; Beglane, Fiona
Abstract: This study investigates the nature of diet in a predominantly Late Medieval Gaelic Irish skeletal population and explores whether any sex-based and/or age differences were evident in the population. A smaller sub-sample was also examined to determine whether there was any evidence for dietary change over time between the Early Medieval ( c .700– c .1200) and Late Medieval periods ( c .1200– c .1600). The dietary evidence was derived using a multiproxy approach that combined information from dental palaeopathology ( n  = 356 adults) and analysis of carbon ( δ 13 C) and nitrogen ( δ 15 N) stable isotope compositions ( n  = 72 individuals). A higher proportion of females were affected by carious lesions when compared to males. This is possibly suggestive of differing levels of carbohydrate consumption between the sexes, although other factors such as eating habits, and genetic and physiological differences may also have influenced the patterns in the data. The isotopic values indicated that both sexes were consuming similar amounts and types (marine vs . terrestrial) of dietary protein. Elevated δ 15 N indicated breastfeeding among the youngest in society but, once children had been weaned, the dietary protein was isotopically similar across the different age categories. Among a smaller radiocarbon-dated sub-sample ( n  = 37), there was an increase in both the percentage of individuals affected by dental caries and the percentage of teeth affected by dental caries between the Early Medieval and Late Medieval periods. This increase may indicate a greater inclusion of plant-based carbohydrates, such as cereals, in the diet over time, although it may also reflect the younger age distribution of the Early Medieval sample. Interpretations for each of these patterns are discussed with reference to the historical and archaeological evidence. Multiproxy palaeodietary studies for Medieval Ireland are limited and this is the first substantial study of evidence derived from both dental palaeopathology and stable isotope analysis. Highlights: Diet in Late Medieval Gaelic Ireland was explored using a multiproxy approach. Data were derived from an analysis of dental palaeopathology, and carbon and nitrogen stable isotope compositions. These were interpreted using historical and archaeological sources for contextual information. Diet comprised cereals, animal products, and a small, but significant contribution from aquatic protein sources. Children, once weaned, had a very similar diet to the adult population. Continuity was apparent in the diet between the Early Medieval and Late Medieval periods.